In vivo study of a biodegradable orthopedic screw (MgYREZr-alloy) in a rabbit model for up to 12 months. (January 2014) - Waizy, Hazibullah; Diekmann, Julia; Weizbauer, Andreas; Reifenrath, Janin; Bartsch, Ivonne; Neubert, Volkmar; Schavan, Robert; Windhagen, Henning
Biodegradable magnesium-based implants are currently being developed for use in orthopedic applications. The aim of this study was to investigate the acute, subacute, and chronic local effects on bone tissue as well as the systemic reactions to a magnesium-based (MgYREZr-alloy) screw containing rare earth elements. The upper part of the screw was implanted into the marrow cavity of the left femora of 15 adult rabbits (New Zealand White), and animals were euthanized 1 week, 12 weeks, and 52 weeks postoperatively. Blood samples were analyzed at set times, and radiographic examinations were performed to evaluate gas formation. There were no significant increased changes in blood values compared to normal levels. Histological examination revealed moderate bone formation with direct implant contact without a fibrous capsule. Histopathological evaluation of lung, liver, intestine, kidneys, pancreas, and spleen tissue samples showed no abnormalities. In summary, our data indicate that these magnesium-based screws containing rare earth elements have good biocompatibility and osteoconductivity without acute, subacute, or chronic toxicity.